2020
DOI: 10.1080/17565529.2020.1737796
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural aspects of farmers’ perception of the risk of climate change and variability in Central Ethiopia

Abstract: Socio-cultural aspects of farmers' perception of the risk of climate change and variability in Central Ethiopia Etana, Dula; van Wesenbeeck, Cornelia F.A.; de Cock Buning, Tjard

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…The joint empirical frequency distribution is defined from observed values of the explanatory variables. Then, conditional frequency distributions are derived from this joint distribution by partitioning the answers by, e.g., S respondents indexed s into a vector y of a dependent variable and a vector x of explanatory variables, taking the frequencies of y conditional on x [41][42][43].…”
Section: Analysis Of Convergence and Divergence Using Pollingmentioning
confidence: 99%
“…The joint empirical frequency distribution is defined from observed values of the explanatory variables. Then, conditional frequency distributions are derived from this joint distribution by partitioning the answers by, e.g., S respondents indexed s into a vector y of a dependent variable and a vector x of explanatory variables, taking the frequencies of y conditional on x [41][42][43].…”
Section: Analysis Of Convergence and Divergence Using Pollingmentioning
confidence: 99%
“…Some studies on Ethiopia have indicated that the RCMs show bias at higher elevations, but work well for low-elevation regions (Workua et al, 2018;Dibaba et al, 2019;van Vooren et al, 2019). Most of the previous studies on Ethiopia have concentrated on climate-change vulnerability and mitigation measures (Eshetu et al, 2020;Etana et al, 2020). Some studies that have focused on the impact of climate change using single RCMs should perhaps re-assess these based on multiple model ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…Second, while the debate on food security continues, ongoing discussions concern the implications of frequent temperature variations, rainfall variability, and increased climatic events across African countries (Etana et al, 2021;Hulme et al, 2001;Nicholson et al, 2000;Nicholson, 2001;Owusu et al, 2021). Although Africa is considered a minor player in total global greenhouse gas emissions, generating less than 4% of the world's total (Oliver & Peters, 2020), the continent is susceptible to the adverse consequences of climate change variability (Boko et al, 2007;Lobell et al, 2011;Nakhooda et al, 2011;Sy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Easterling et al (2007), a rise in temperature by 3 °C or more will cause food prices to increase by 40%. A large proportion of the African population relies on rain-fed farming for their livelihood (Adhikari et al, 2015;Cooper et al, 2008;Muchuru & Nhamo, 2019), so extreme climate variability poses a significant threat to food production (Boko et al, 2007;Etana et al, 2021;Lobell et al, 2011;Schlenker & Lobell, 2010). Climate change and variability also raise food production costs, translating to high consumer prices (Berrera & Hertel, 2021;Dadzie et al, 2021;FAO, 2008).…”
Section: Introductionmentioning
confidence: 99%